FXR deficiency alters bile acid pool composition and exacerbates chronic alcohol induced liver injury. Issue 4 (April 2019) - Kong, Bo; Zhang, Min; Huang, Mingxing; Rizzolo, Dan; Armstrong, Laura E.; Schumacher, Justin D.; Chow, Monica D.; Lee, Yi-Horng; Guo, Grace L.
Abstract: Recent studies have investigated the roles of FXR deficiency in the pathogenesis of alcoholic liver disease (ALD). However, the underlying molecular mechanisms remain unclear. In this study, FXR knockout (FXR −/− ) and wild-type (WT) mice were subjected to chronic-plus-binge alcohol feeding to study the effect of FXR deficiency on ALD development. The degree of liver injury was greater in FXR −/− mice compared to WT mice. Ethanol feeding enhanced hepatic steatosis in FXR −/− mice, accompanied by decreased mRNA levels of Pparα and Srebp-1c . The expression of Lcn2 was increased by ethanol treatment, despite unchanged expression of pro-inflammatory cytokines Tnfα, Il6 and Il-1β . Furthermore, ethanol treatment altered bile acid (BA) homeostasis to a greater extent in FXR −/− mice, as well as serum and hepatic BA pool composition. The mRNA levels of hepatic Cyp7a1 and Shp, as well as intestinal Fgf15, were decreased in WT mice with ethanol feeding, which were further reduced in FXR −/− mice. Levels of both primary and secondary BAs were markedly elevated in FXR −/− mice, which were further increased after ethanol treatment. Moreover, hepatic MAPK signaling pathways were disturbed presumably by increased hepatic BA levels. In summary, FXR deficiency increased hepatic steatosis and altered BA pool composition, contributing to worsened liver toxicity.